Design and Performance Analysis of Institutional Cooking Stove for High Hill Rural Community of Nepal - Adhikari, Prabidhi; Adhikari, Aashish; Dhital, Shree Krishna; Shrestha, Bijendra; Dura, Hari Bahadur (Kathmandu University Journal of Science, Engineering and Technology, 2020)
Increasing dependency on the firewood due to increasing population in the rural community of Nepal has resulted in many adverse effects on energy, environment, and human health. Due to the large demand for energy, various technologies have been incorporated into stoves to increase their efficiency and reduce health risks. The paper focuses on the design and fabrication of a durable stove using proper orientation of insulating bricks considering technical, social, and economic factors. A single-pot institutional ICS designed with parameters under the "Nepal Interim Benchmark for the Solid Biomass Cookstove 2016" protocols was fabricated and tested at the Biomass Stove Testing Lab, Kathmandu University, under "No wind condition". A total of 12 bricks along with a mild steel top plate of 3mm and a properly insulated chimney were used to fabricate the stove. Water Boiling Tests (WBT) were conducted under the national stove testing protocol. Thermal efficiency, fuel consumption rate, burning rate, firepower, and turn-down ratio are parameters used to determine the performance of the stove. Thermal efficiency was recorded at 31% using Alnus nepalensis, a fuel, with an average moisture content of 13% on a wet basis. The emission test was carried out using the Indoor Air Pollution Meter (IAP Meter) from Aprovecho Research Center, USA. The test was conducted along with the WBT test following the standard test protocols. The general average PM concentration was found to be 109 µg/m³, and the average CO concentration was 3.6 ppm.